TEATRO MUSICAL PARA EL DESARROLLO DE LA MOTRICIDAD GRUESA EN LOS NIÑOS DE 04 AÑOS DE LA INSTITUCIÓN EDUCATIVA INICIAL N° 028 “MIGUELITO ALBERTO REYNA ZUBIATE” - CHACHAPOYAS 2023 - Abanto Flores, Santos Jobita (2023)
The purpose of this research is to analyze the impact of musical theater on the progress of gross motor skills in four-year-old children. A quantitative approach of an applicative nature was adopted, with a pre-experimental design. The sample included 21 preschool children between the ages of 4 and 5 years old. The instrument used to collect data was an evaluation rubric. Our didactic strategy "Musical Theater", a playful and creative tool based on dramatizations, dances and songs, fostering progress in motor skills. The results of the pre-test revealed that 38% of the children have reached the "beginning" level of achievement, while 62% have obtained the "process" level of achievement. On the other hand, the results obtained from the post-test showed that 14% of the children reached the "process" level, 71% were at the "achieved" level, and 14% obtained the "outstanding" level. These results guarantee that musical theater is an effective resource to promote the development of gross motor skills in childhood. Keywords: Gross motor skills, musical theater, pedagogical strategy, creativity and child developm